2002
DOI: 10.1074/jbc.m110047200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Developmentally Expressed Proteins That Functionally Interact with Nedd4 Ubiquitin Ligase

Abstract: Nedd4 is a HECT domain-containing ubiquitin ligase that mediates ubiquitylation and proteasome degradation of target proteins. The molecular basis for the interaction of Nedd4 with substrates lies in its WW domains, which can bind proline-rich (PY) domains in target proteins. Nedd4 is a developmentally expressed protein and may have a fundamental role to play in embryonic processes. However, whether Nedd4 has such a function is currently unknown, in part because few developmentally regulated ubiquitylation sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 43 publications
1
70
0
Order By: Relevance
“…45 Interaction mapping suggested that the N-terminal domain of N4BP1 is required to bind Nedd4 and possibly involves the UBA domain. 44 These observations suggest that the N4BP1 represents an unusual cellular target for monoubiquitination, which might help to assemble into nuclear RNA processing complexes. The presence of the UBA domain in the N4BP1 and KIAA1726, thus provide the first evidence for the possible involvement of Nedd4-dependent monoubiquitination in nuclear RNA processing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…45 Interaction mapping suggested that the N-terminal domain of N4BP1 is required to bind Nedd4 and possibly involves the UBA domain. 44 These observations suggest that the N4BP1 represents an unusual cellular target for monoubiquitination, which might help to assemble into nuclear RNA processing complexes. The presence of the UBA domain in the N4BP1 and KIAA1726, thus provide the first evidence for the possible involvement of Nedd4-dependent monoubiquitination in nuclear RNA processing.…”
Section: Resultsmentioning
confidence: 99%
“…It gets monoubiquitinated by a Nedd4 and a HECT domain ubiquitin ligase both in vitro and in vivo. 44 Monoubiquitination of N4BP1 does not cause it to be degraded by the proteasome and it localizes to distinct spherical structures in the nucleus, 44 which resemble the punctuate structures associated with RNA processing. 45 Interaction mapping suggested that the N-terminal domain of N4BP1 is required to bind Nedd4 and possibly involves the UBA domain.…”
Section: Resultsmentioning
confidence: 99%
“…E3 ligases of Nedd4 family contain 2-4 tryptophan-based WW domains, which consist of 35-40 amino acids and bind certain proteins containing proline-rich motifs. The WW domains have been reported in a wide variety of proteins of yeast, nematode, vertebrate, and mammalian origins and play a direct role in mediating specific and distinct protein-protein interactions (21)(22)(23).…”
Section: However It Is Not Known How Such Tight Regulation Is Realizmentioning
confidence: 99%
“…A murine counterpart for STAG1, Nedd4WW-binding protein 4 (Murillas et al, 2002) appears to be a ubiquitin-protein ligase that is cleaved by caspases during apoptosis (Harvey et al, 1998). Nedd4 in the mouse may be required to mediate the normal turnover of proteins required for apoptotic function.…”
Section: Stag1 As a Target Of P53-121fmentioning
confidence: 99%